Analysis of centrosome overduplication in correlation to cell division errors in high-risk human papillomavirus (HPV)-associated anal neoplasms - Duensing, Anette (2007)
High-risk HPV-associated anal neoplasms are difficult to treat and biomarkers of malignant progression are needed. A hallmark of carcinogenic progression is genomic instability, which is frequently associated with cell division errors and aneuploidy. The HPV-16 E7 oncoprotein has been previously shown to rapidly induce centriole and centrosome overduplication and to cooperate with HPV-16 E6 in the induction of abnormal multipolar mitoses. Based on this function, it has been suggested that HPV-16 E7 may act as a driving force for chromosomal instability. However, a detailed analysis of centrosome overduplication in primary HPV-associated neoplasms has not been performed so far. Here, we determined the frequency of centrosome overduplication in HPV-associated anal lesions using a recently identified marker for mature maternal centrioles, Cep170. We detected centrosome overduplication in a small but significant fraction of cells. Remarkably, centrosome overduplication, but not aberrant centrosome numbers per se or centrosome accumulation, correlated significantly with the presence of cell division errors. In addition, our experiments revealed that in particular pseudo-bipolar mitoses may play a role in the propagation of chromosomal instability in high-risk HPV-associated tumors. These results provide new insights into the role of centrosome aberrations in cell division errors and encourage further studies on centrosome overduplication as a predictive biomarker of malignant progression in HPV-associated anal lesions.